Acute and sub-acute toxicity studies of hydroalcoholic extract from Acacia suma (Roxb) (Fabaceae) stem barks - Sumanta Mondal; Padilam Suresh; Gubbiyappa Shiva Kumar; Suvendu Kumar Sahoo; Naresh Panigrahi (International Journal of Phytomedicine, 2012)
Herbal medicines are popular remedies for diseases used by a vast majority of the world’s population. The pharmacological effects of many plants have been studied in various laboratories, whereas there are many limitations regarding the safety and efficacy. Our research group has previously investigated the phytochemical and pharmacological properties of this plant. The present study was carried out to evaluated acute and subacute toxicity of hydroalcoholic extract from stem bark of Acacia suma (Roxb.) var. Acacia polyacantha (Family- Fabaceae). Acute toxicity study was evaluated on male Swiss albino mice (20-25g) and Wistar albino rats (150-200g) were assigned for sub-acute toxicity, after ingestions of the extract during one day (acute model) and during 15 days (subacute model). The acute toxicity studies were conducted as per the OECD guidelines 423, where the limit test dose of 3000 mg/kg b.wt., p.o., used. Results showed that the LD50 of the extract is higher than 3000 mg/kg b.wt., and there was no mortality was observed at 3000 mg/kg b.wt., p.o., dose except with prominent diuresis and purgation, these toxic sign are probably due to the saponins content of the extract; so, testing of the hydroalcoholic extract of Acacia suma stem bark at higher dose was practically non-toxic. In sub-acute toxicity study, the extract treated groups (300 and 600 mg/kg b.wt., p.o.) did not show any significant changes in body weight when compared to the control group. The weight of the liver, kidney and pancreas were found to be unaltered in the experimental groups compared with the control group. The haematological and biochemical parameters (hepatic and renal function tests) did not show any significant changes in the sample treated groups when compared with the control group animals.